Guilt for perceiving oneself as a burden in healthy older adults. Associated factors. (2nd December 2021) - Pedroso-Chaparro, María del Sequeros; Márquez-González, María; Vara-García, Carlos; Cabrera, Isabel; Romero-Moreno, Rosa; Barrera-Caballero, Samara; Losada, Andrés
Abstract: Introduction . Negative self-perceptions of aging can trigger self-perception as a burden and guilt associated with perceiving oneself as a burden in older adults who do not have physical or cognitive limitations. The main objective of this study was to analyze the role of negative subjective perception of aging, perceived control, self-perceived burden and depressive symptomatology in the explanation of guilt associated with perceiving oneself as a burden to others in older adults who do not show physical or cognitive limitations. Methods: Participants were 317 community-dwelling people over 60 years without cognitive or functional limitations. A path model that explores the role of self-perceived burden in the relationship between negative self-perception of aging, perceived control, depressive symptoms and guilt associated with self-perception as a burden was analyzed. Results: The model presented excellent fit to the data, explaining 41% of the depressive symptomatology and 45% of guilt for perceiving oneself as a burden. Negative self-perceptions of aging, lower sense of control, and a perception of being a burden were significantly associated with depressive symptoms and guilt for perceiving oneself as a burden. Discussion: This study documents potential correlates of psychological distress in older adults with no explicit physical or cognitive problems, suggesting paths through which feelings of guilt for perceiving oneself as a burden may be reported by this population.